O VAR e o tempo : a dinâmica das transmissões esportivas com a utilização do árbitro de vídeo - Barros, Mateus Kerr de (2019)
In this document, we want to find out what`s changing in the sports teletransmissions with the VAR´s arrival - the Video Assistant Referee, in football. We´re trying to understand how the sports dynamic, affected due to the arise of the new eletronic resources, will be showed on the tv stations. Will the experience of watch a football match in a television be the same? How the broadcasters are working with these new elements and how they´re been put in their narratives? To understand: VAR (Video Assistant Referee) is an eletronic system developed to help the football referees, and it was used for the first time in a World Cup in 2018, Russia. A team formed by one Video Referee and three assistants worked in each one of the 64 matches of this championship. These professionals worked in a big studio, installed in Moscow during the competition. Through this document, we analysed 18 situations of 14 different matches where the eletronical system was required. We´d selected this situations of the football game due to their ineditism or historical relevance. We concluded that the teletransmition followed certain patterns, but some "noises", like we use to say in the TV vocabulary, have difficulted the understanding process of the viewers in some cases. We also brough some questions that might be modified to turn the VAR product into something more atractive and with more transparency.